Use of fluorescent staining and flow cytometry for monitoring physiological changes in solventogenic clostridia - Patakova, Petra; Linhova, Michaela; Vykydalova, Pavla; Branska, Barbora; Rychtera, Mojmir; Melzoch, Karel (Anaerobe, 2014)
Physiological changes in populations of Clostridium beijerinckii and Clostridium tetanomorphum were monitored by fluorescence staining and flow cytometry. To estimate the number of metabolically active cells in exponential growth, a combination of the dyes propidium iodide and carboxy fluorescein diacetate appeared to be a good choice for both species. During stationary phase, these stains did not reflect physiological changes sufficiently and therefore additional labeling with bis-(1,3-dibutylbarbituric acid) trimethineoxonol was applied. Results of fluorescence staining in solventogenic batch fermentations were compared with substrate-use data, the concentration of key metabolites and growth curves. We demonstrate that measurements by all methods were mutually compatible.
Keywords: Fluoresceins; Isoxazoles; fermentace; barbituráty; Clostridium; barvení a značení; isoxazoly; Fermentation; fluorescenční barviva; Fluorescent Dyes; fluoresceiny; Flow Cytometry; Propidium; propidium; Batch Cell Culture Techniques; techniky vsádkové kultivace; Bioreactors; průtoková cytometrie; Barbiturates; bioreaktory; Staining and Labeling